Introduction to basic concepts of analytical chemistry - Sulaiman, Yusran; Abdullah, Jaafar; Mohd Zawawi, Ruzniza; Kamaruzaman, Sazlinda; Yusof, Nor Azah (Universiti Putra Malaysia Press, 2017)
Analytical chemistry is an important area, particularly in the industrial sector, agriculture, health and the environment. This book is written with the aim to provide basic concepts in analytical chemistry which involves titration, gravimetry, solvent extraction, chromatography, electrochemical methods, thermal analysis and data analysis. The contents in this book are designed in a simple way with several examples that suitable for students, academicians and researchers.